2003
DOI: 10.1038/sj.bjc.6601320
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of intralesional therapy with interleukin-2 in soft-tissue melanoma metastases

Abstract: The objective of the present study was to validate the use of intralesional injection of interleukin-2 (IL-2) in patients with skin and softtissue melanoma metastases. A total of 24 patients with AJCC stage III or IV melanoma and single or multiple skin and soft-tissue metastases were included. Interleukin-2 injections were administered intralesionally into the total number of cutaneous and soft-tissue metastases accessible from the skin, 2 -3 times weekly, over 1 -57 weeks. Single doses varied from 0.6 to 6 Â… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 28 publications
(28 reference statements)
3
106
0
4
Order By: Relevance
“…However, there was no evidence of clinically meaningful systemic immune activation since regression of nontreated lesions was not observed in any patient [35]. Similar findings have been observed in patients treated with intralesional IL-2, which leads to frequent regressions of treatment lesions but not abscopal regressions of untreated lesions [36,37]. These findings are interesting but inadequate since the goal of cytokine therapy is to induce systemic immune changes that alone or in combination with additional agents could lead to durable remissions in cancer patients.…”
Section: Il-12 As a Cancer Therapeuticsupporting
confidence: 69%
“…However, there was no evidence of clinically meaningful systemic immune activation since regression of nontreated lesions was not observed in any patient [35]. Similar findings have been observed in patients treated with intralesional IL-2, which leads to frequent regressions of treatment lesions but not abscopal regressions of untreated lesions [36,37]. These findings are interesting but inadequate since the goal of cytokine therapy is to induce systemic immune changes that alone or in combination with additional agents could lead to durable remissions in cancer patients.…”
Section: Il-12 As a Cancer Therapeuticsupporting
confidence: 69%
“…In previous studies using untargeted IL2, we reported CRs of injected metastases, according to adapted RECIST criteria, in more than 60% of patients (14,15), which is significantly higher than the CR rate of 25% according to modified irRC/RECIST observed here. In our opinion, this difference does not reflect a lower efficacy of L19-IL2 compared with untargeted IL2, but is more likely related to differences in the patient populations and trial designs.…”
Section: Discussionmentioning
confidence: 56%
“…Second, there are differences between the studies with untargeted IL2 and the present study in the treatment regimen and schedule. In IL2-based studies, the treatment schedule was two to three times weekly with a maximum daily dose of 16 MIU IL2 or variable, according to the individual tumor burden of patients (14,15). Importantly, in these trials, new lesions arising during treatment were also injected, and treatment continued until all lesions, including the new ones, finally regressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impressive results have been obtained on cutaneous metastases of melanoma patients (27,28). Our approach focuses on the search for synergic combinations of various cytokines and TLR ligands with the aim of obtaining immune rejection with much lower dosages (50-500×) than those reported previously.…”
Section: Discussionmentioning
confidence: 99%